Relationship between aortic valve stenosis and the hemodynamic pattern in the renal circulation, and restoration of the flow wave profile after correction of the valvular defect. Issue 9 (September 2020) - Bardelli, Moreno; Cavressi, Monica; Furlanis, Giulia; Pinamonti, Bruno; Leone, Mariafontana; Albani, Stefano; Korcova, Renata; Fabris, Bruno; Sinagra, Gianfranco
Objective: The index of maximal systolic acceleration ([AImax]: maximal systolic acceleration of the Doppler waveform divided by peak systolic velocity) shows diagnostic accuracy in screening of renal artery stenosis. This study aimed to determine whether an upstream factor of resistance, such as aortic valve stenosis (AVS), can affect Doppler parameters detected in the peripheral arteries. Methods: In this prospective study, we measured the AImax in non-stenotic renal interlobar arteries of 62 patients with AVS. Patients were divided into three groups on the basis of severity of valvulopathy as follows: mild-to-moderate AVS (M-AVS; n = 24), intermediate AVS (I-AVS; n = 15), and severe AVS (S-AVS; n = 23) based on Nishimura's criteria. Results: The AImax in the renal parenchymal arteries was significantly lower in the S-AVS group (8.9 ± 3.6 s −1 ) than in the M-AVS (15.3 ± 3.8 s −1 ) and I-AVS groups (16.7 ± 5.2 s −1 ). The AImax was positively correlated with the aortic valve area and inversely correlated with the tranvalvular aortic pressure gradient. After aortic valve replacement, the AImax significantly increased from 10.7 ± 4.0 s −1 at baseline to 19.3 ± 4.4 s −1 . Conclusions: Proximal resistance can lead to diagnostic bias of Doppler parameters that are applied in the diagnosis of peripheral vasculopathies, particularly in renal artery stenosis.